Kajian Dan Rancang Bangun Alat Pakan Ikan Otomatis (Smart Feeder) Pada Kolam Budidaya Ikan Berbasis Internet Of Things - Gunawan, Indra; Ahmadi, Hamzan (Fakultas Teknik Universitas Hamzanwadi, 2024)
In fish farming, the timing of fish feeding is very important, fish need regular and continuous feed. Feed is a component in fish farming that is useful for growth, so feeding is fundamental in fish farming. Overfeeding can increase production costs and degrade water quality. Fish farmers often have to do several activities at the same time, which can lead to errors in the amount of fish feed. This results in large feed costs and decreased pond water quality. Seeing these problems, a study was conducted that aims to create a tool that can monitor water quality and automatic fish feeders using Internet of Things (IoT) technology that functions to monitor feed schedules and water quality conditions that can be seen through applications on smartphones, in addition to monitoring water quality and automatic feeders, it can also display log data on the amount of fish feed that has been given, fish feed is running out and water turbidity conditions have reached more than 25 NTU. At the time of testing, the tool has worked well, the tool can monitor the amount of feed, and Turbidity sensor can read the level of water turbidity, this tool can also send realtimei information well, the time required in sending information on the application is ± 2 seconds